Institutional ownership, board of directors and yield spreads in Long- and medium-term corporate bonds and sukuk - Noriza M.S.; Haniff M.N.; Ali N. (Kolej University Islam Sultan Azlan Shah, 2023)
Previous studies documented that type of investor significantly affects the performance of bonds and sukuk. These studies showed that the yield to maturity (YTM) of bonds and sukuk are significantly associated with institutional investors. This association is because institutional investors actively monitor the performance of bonds and sukuk. Apart from the type of investor, the roles played by the board of directors (BOD) in decision making significantly influence the performance of bonds and sukuk, especially the YTM. This study aims to investigate the relationship between institutional ownerships and the BOD and yield spreads of long- and medium-term corporate bonds and sukuk. Data are obtained from firm issuers' annual reports, Bond Info Hub of Malaysia Central Bank, Department of Malaysia Statistics and Bloomberg from 2000 to 2014. The study employed unbalanced panel data approach for multivariate robust regression, OLS, fixed-effect, and random-effect models. Results revealed that the presence of top-six institutional investors and characteristics of the BOD exert a significant negative effect on the yield spreads. The findings are also consistent with the agency cost of debt theory, which suggests that long-term bonds carry a lower cost of defaults than medium-term bonds. 2018 Kolej University Islam Sultan Azlan Shah.